1998
DOI: 10.1021/la9802062
|View full text |Cite
|
Sign up to set email alerts
|

Surface Thermodynamics of Hematite/Yttrium Oxide Core−Shell Colloidal Particles

Abstract: Spherical and quite monodisperse particles (average diameter 60 ( 7 nm) of hematite (R-Fe2O3) were synthesized and then covered with a shell of yttrium oxide of variable thickness. A surface thermodynamic study was carried out for these core/shell colloidal particles, using two experimental techniques: contact angle measurements of selected liquids on glass slides uniformly covered by the material and determination of the penetration rates of liquids through thin layers of the solid. Using van Oss et al.'s mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 28 publications
4
21
0
Order By: Relevance
“…1 and the diffractograms of Fig. 2 suggest, as mentioned above, an increasing efficiency of the coating in the order A < B < C; in our previous investigation on the electrical and thermodynamic properties of the particle/aqueous solution interface (13,14), it was found that sample C showed a behavior most similar to that of yttrium oxide, whereas sample A was more similar to hematite, and type B particles behaved in a somewhat intermediate way. Our susceptibility data in Fig.…”
Section: Figsupporting
confidence: 64%
See 1 more Smart Citation
“…1 and the diffractograms of Fig. 2 suggest, as mentioned above, an increasing efficiency of the coating in the order A < B < C; in our previous investigation on the electrical and thermodynamic properties of the particle/aqueous solution interface (13,14), it was found that sample C showed a behavior most similar to that of yttrium oxide, whereas sample A was more similar to hematite, and type B particles behaved in a somewhat intermediate way. Our susceptibility data in Fig.…”
Section: Figsupporting
confidence: 64%
“…This is the main aim of this work, in which spherical hematite (α-Fe 2 O 3 ) particles are covered by a shell of Y 2 O 3 . In previous works (13,14), it was found that the surface properties (electrical, thermodynamic, chemical) were essentially controlled by the shell. It was expected that, in contrast, the magnetism of these composite units would be controlled by the core: the particles with mixed composition would thus show interesting properties, behaving as Y 2 O 3 in all phenomena related to the particle surface, and as α-Fe 2 O 3 in their response to applied magnetic fields.…”
Section: Introductionmentioning
confidence: 97%
“…Concerning γ − S , it shows large values in magnetite (like in many other inorganic oxides, for instance hematite and yttria, as found in Ref. (38)), which is thus essentially a monopolar, electron-donor material. Its value of γ − S is much larger than that found for PLA (almost zero); when magnetite is covered by a layer of PLA, γ − S is significantly reduced, another proof of the presence of the polymer on the oxide particles.…”
Section: Surface Thermodynamicsmentioning
confidence: 53%
“…In addition, the Lifshitz-van der Waals component of the mixed particles is almost the same as that of the cyanoacrylate polymer, although this component is the least affected (as is usually the case, see, e.g., Ref. [40]). The electron-donor component γ − S shows large values in carbonyl iron (like in many other inorganic oxides, for instance hematite, yttria and magnetite, as found in Refs.…”
Section: Surface Thermodynamicsmentioning
confidence: 66%